Rapidly derived colorectal cancer cultures recapitulate parental cancer characteristics and enable personalized therapeutic assays. Issue 1 (7th July 2014) - Ashley, Neil; Jones, Matthew; Ouaret, Djamila; Wilding, Jenny; Bodmer, Walter F
Abstract We have developed a simple procedure for deriving pure cultures of growing cancer cells from colorectal cancers, including material refrigerated overnight, for pathological characterization and cytotoxicity assays. Forty‐six cancers were processed and cultures set up under varying culture conditions. Use of a Rho kinase (ROCK1) inhibitor markedly increased culture survival, resulting in 80% of samples growing in culture for at least 1 month and beyond. Overnight refrigeration of samples before culture initiation had little effect on success rates, paving the way for cultures to be established for samples collected over wide geographical areas, such as those for clinical trials. Primary cultures demonstrated good correlation for differentiation markers compared to parent cancers, and were highly dynamic in 3D culture. In Matrigel, many colonies formed central lumens, indicating the presence of stem‐like cells. Viable colonies in these cultures recapitulated the in vivo generation of carcinoembryonic antigen (CEA)‐positive necrotic/apoptotic debris, much of which was derived from abnormal vacuolated dynamic 'bubble cells' that have not previously been described. Although bubble cells morphologically resembled signet ring cells, a rare cancer subtype, immunostaining suggested that they were most likely derived from terminally differentiated enterocytes. Micro‐assays showed that drug toxicity could be measured in these cultures within hours and with sensitivity down to a few hundred cells. Primary cultures derived by our method provide valid in vitro avatars for studying the pathology of cancers in vitro and are amenable to pre‐clinical drug testing, paving the way for personalized cancer treatment. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.